Mathematical model assessment and forecasting reliability software - managed data protection government communications system - Гнатюк, Сергій Євгенович (Ukrainian Information Security Research Journal, 2016)
The work is dedicated to improving the mathematical models assessing the reliability of software-driven information security in state governmental communication system by installing and using the new functional relationships and analytical expressions and algorithms for calculating the coefficients to improve the accuracy of forecasting performance indicators. Based on the proposed models using the method of estimation and forecasting of the indicators of reliability of software-driven information security, which allows to evaluate system reliability with regard to hardware and software. Complex specified using the proposed method for estimating parameters of reliability systems for government communications, which unlike existing quantitatively assesses the probability of connectivity customers with regard to software reliability communications.